Book Review: Ecotourism and Environmental Sustainability: Principles and Practice. (20th July 2010) - Scherrer, Pascal
Ecotourism and Environmental Sustainability: Principles and Practice, by J. Hill and T. Gale (Eds.). Ashgate, 2009. ISBN: 978-0-7546-7262-3